Pretransplant Cytomegalovirus-Specific Cellular Immunity and Risk of Viral Reactivation Following Lung Transplantation: A Prospective Cohort Study. (4th December 2020) - Altaf, Mohammed; Lineburg, Katie E; Crooks, Pauline; Rehan, Sweera; Matthews, Katherine K; Neller, Michelle A; Ambalathingal, George R; Sinha, Debottam; Grant, Michelle; Hopkins, Peter M A; Chambers, Daniel; Khanna, Rajiv; et al.
Abstract: Cytomegalovirus (CMV) remains a significant burden in lung transplant recipients. Deficiencies in T-cell immunity posttransplant increase the risk of CMV-associated complications. However, it is not clear if underlying poor pretransplant immunity increases risk. To assess this, we recruited 39 prospective lung transplant patients and performed QuantiFERON-CMV on their peripheral blood. More than a third of prospective CMV-seropositive transplant recipients were CMV non-immune reactive (CMV-NIR) pretransplant. CMV-NIR status was associated with a significantly higher incidence of CMV reactivation posttransplant, demonstrating that dysfunctional CMV immunity in prospective lung transplant recipients is associated with an increased risk of viral reactivation posttransplant.